Carbon-coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
By using carbon nanotubes and organic carbon sources in the positive electrode materials of sodium ion batteries, the problem of poor conductivity and electrochemical performance of the positive electrode materials of sodium ion batteries is solved, and the material conductivity is realized The improvement of structural rigidity has promoted the industrial application of sodium ion batteries.
Patent Information
- Application Number
- CN202411428831.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The conductivity and electrochemical performance of the positive electrode material of sodium ion battery are poor, resulting in obstacles in the industrial development.
By using carbon nanotubes and organic carbon sources as carbon sources, carbon-coated sodium ferrophosphate phosphate particles were prepared, mixed in proportion and sintered to form a carbon-coated sodium ferrophosphate positive electrode material. The carbon layer of this material contains carbon nanotubes and organic carbon sources, forming a strong conductive network, improving the conductivity and structural rigidity of the material.
This technical method not only improves the conductivity of the positive electrode material of sodium ion battery, but also enhances the overall structural rigidity of the material, significantly improves the electrochemical performance, and promotes the industrial application of sodium ion battery.
Smart Images

Figure CN119495724A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a carbon-coated sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries, as a clean and efficient energy storage medium, are used as positive electrode materials in digital 3C, energy storage power stations, power vehicles and other scenarios. At the same time, due to the scarcity of lithium resources, especially the fact that most resources are distributed abroad, and the increasing demand from corresponding industries at home and abroad, lithium carbonate, one of its raw materials, has soared, including the current mainstream ternary lithium and lithium iron phosphate in the market, which has greatly increased the manufacturing cost of lithium-ion batteries.
[0003] Sodium-ion batteries have the potential to replace lithium-ion batteries because of their abundant earth reserves and the similar chemical properties of sodium and lithium. However, since the radius of sodium ions is naturally larger than that of lithium ions, it is more difficult to deintercalate and deintercalate sodium ions, resulting in poor electronic conductivity and low specific capacity, which has become the main factor restricting its industrial development. Sodium ferric pyrophosphate has low cost, good structural stability, and excellent cycle performance. It is one of the ideal choices for sodium ion battery positive electrode materials with industrial application prospects. However, due to the low inherent electronic conductivity of ferric pyrophosphate, it needs to be modified by carbon coating. Summary of the invention
[0004] The technical problem to be solved by the present invention is: how to improve the conductivity and electrochemical performance of the positive electrode material of the sodium ion battery by carbon coating modification. The present invention prepares two kinds of sodium iron phosphate pyrophosphate particles using carbon nanotubes and organic carbon sources as carbon sources respectively, mixes the two kinds of particles in proportion and then sinters them to obtain a carbon-coated sodium iron phosphate pyrophosphate positive electrode material. In the carbon layer coated on the surface of the material, the carbon nanotubes and the organic carbon source play their respective conductive advantages to form a strong conductive network, which not only improves the conductivity of the material, but also enhances the overall structural rigidity of the material.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a carbon-coated sodium iron phosphate pyrophosphate positive electrode material, comprising a sodium iron phosphate pyrophosphate matrix and a coating layer on the surface, wherein the coating layer is a carbon coating layer, the coating layer content in the positive electrode material is 2 to 10%, and carbon nanotubes are also distributed in the carbon coating layer to form a conductive network.
[0006] The carbon coating layer is also doped with nitrogen, and the content of nitrogen in the positive electrode material is 0.1-0.3%.
[0007] The above-mentioned method for preparing a carbon-coated sodium iron phosphate pyrophosphate positive electrode material comprises the following steps:
[0008] S1: weigh carbon nanotubes, inorganic carbon source, and dispersant, dissolve them in deionized water to obtain a mixed solution, weigh iron source, sodium source, phosphorus source, and chelating agent, add them to the mixed solution, stir evenly, and then spray dry to obtain sodium iron pyrophosphate particles A;
[0009] S2: Weigh an iron source, a sodium source, a phosphorus source, and an organic carbon source, mix them, grind them in a deionized water medium, and then dry them to obtain sodium iron pyrophosphate particles B;
[0010] S3: Particles A and B are mixed to obtain a precursor material, which is then sintered and air flow-milled to obtain a carbon-coated sodium iron phosphate pyrophosphate positive electrode material.
[0011] Preferably, the content of carbon nanotubes in the mixed solution of step S1 is 5-10%, the content of inorganic carbon source is 0-5%, the content of dispersant is 0.5-2%, the mass ratio of the iron source, sodium source and phosphorus source is 2-3:3-4.5:4, the carbon nanotubes and inorganic carbon source account for 2-6% of the total mass of particle A, and the particle size of particle A is 200-400nm.
[0012] Preferably, in step S1, the inorganic carbon source is one or two of carbon black and acetylene black mixed in any proportion, the dispersant is one or more of polyvinyl pyrrolidone, ethanol, sodium polyacrylate, hydroxyethyl cellulose, and polypropylene ether, and the chelating agent is one or more of oxalic acid, citric acid, phosphoric acid, sodium pyrophosphate, sodium metaphosphate, tartaric acid, and triethyl ethylenediaminetetraacetate.
[0013] Preferably, the solid content of the liquid spray-dried in step S1 is controlled between 10 and 30%, the air inlet temperature is 150 to 300°C, and the air outlet temperature is 85 to 120°C.
[0014] Preferably, in step S2, the mass ratio of the iron source, the sodium source and the phosphorus source is 2-3:3-4.5:4, the organic carbon source accounts for 4-9% of the total mass of the particles B, and the particle size of the particles B is 300-600 nm.
[0015] Preferably, the organic carbon source in step S2 is an organic compound mainly composed of carbon and hydrogen elements, preferably an organic compound containing nitrogen atoms.
[0016] The organic carbon source is one or more of sucrose, glucose, starch, citric acid, vitamin C, polyethylene glycol, and polyvinyl alcohol, preferably one or more of glucosamine, amino starch, amino polyvinyl alcohol, or amino-terminated polyethylene glycol; the drying method is spray drying or oven drying, wherein the inlet air temperature of the spray drying is 150-300°C and the outlet air temperature is 85-120°C; the oven drying temperature is controlled at 60-150°C.
[0017] Preferably, the iron source is one or more of ferric phosphate, ferric pyrophosphate, iron powder, iron oxide powder, ferrous oxalate, ferrous acetate, ferrous sulfate, ferric nitrate, and ferrous chloride; the sodium source is one or more of sodium carbonate, sodium phosphate, sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium acetate, sodium oxalate, sodium bicarbonate, sodium sulfate, and sodium bicarbonate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ferric phosphate, ferric pyrophosphate, manganese phosphate, sodium phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0018] Preferably, in step S3, the mass ratio of particles A to particles B is 1:1-2.5, and the sintering is divided into two or three stages of heating, wherein 100-200°C is kept for 0-60 min, 200-400°C is kept for 60-250 min, and 400-950°C is kept for 600-12000 min, and the sintering atmosphere is an inert atmosphere.
[0019] Application of any of the above carbon-coated sodium iron phosphate pyrophosphate positive electrode materials in sodium ion batteries.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention mixes two materials prepared by different methods and coated with different carbons in proportion and then sinters them, so that carbon is enriched in an amorphous form and coated around the material. Different carbon sources play their respective conductive advantages to form a strong conductive network, which not only improves the conductivity of the material, but also enhances the overall structural rigidity of the material.
[0022] (2) The organic carbon source in the present invention can play a role in refining particles, obtaining nanoparticles with uniform particle size and uniform dispersion, thereby improving the performance of the material; and the inorganic carbon source will form a loose chain-like coating layer on the surface of the material as it decomposes at high temperature, thereby making the material have a larger specific surface area and better compressibility, thereby improving the compaction and energy density of the material. At the same time, due to its relatively large aspect ratio, carbon nanotubes can easily form a conductive grid with the surrounding materials, thereby improving the conductivity of the material.
[0023] (3) By using a nitrogen-containing organic carbon source, in-situ nitrogen doping can be achieved during the calcination process. This method is based on atomic-level doping, which improves the uniformity of doped nitrogen. It can provide more active sites during the sodium ion insertion and extraction process, thereby improving the electrochemical performance of sodium ion batteries.
[0024] (4) The mixed material is sintered and air flow crushed under inert atmosphere to obtain a phosphate pyrophosphate positive electrode material; the purpose of mixing first and then sintering is to allow the materials coated with different carbon layers to be better fused together during the sintering process, thereby forming a uniform coated carbon layer, and at the same time better exert the conductive advantages of the carbon nanotubes, inorganic carbon sources, and organic carbon sources to form a strong conductive network. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 TEM images of materials coated with different carbon sources in Example 1, wherein a is coated with a carbon nanotube-inorganic carbon source composite carbon source; b is coated with glucose;
[0026] Figure 2 XRD pattern of the material prepared in Example 1;
[0027] Figure 3 This is the SEM image of the material prepared in Example 1. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1:
[0031] Preparation of carbon-coated sodium iron phosphate pyrophosphate cathode material;
[0032] S1: Weigh 3 parts of carbon nanotubes (tube diameter 10-50nm), 2 parts of carbon black, 1 part of polyvinyl pyrrolidone, and 94 parts of deionized water, and disperse them uniformly in a high-speed disperser to obtain a mixed solution; weigh ferric nitrate, sodium acetate, ammonium dihydrogen phosphate, and oxalic acid (wherein the mass ratio of Na:Fe:P is 4.2:2.8:4, and the mass of oxalic acid is 1.5% of the total mass) and add them to the mixed solution so that the sum of the content of carbon nanotubes and carbon black is 5% of the total solid content, and at the same time add deionized water so that the total solid content is 15%, and disperse them uniformly in a high-speed disperser to obtain a feed solution;
[0033] Spray drying: set the inlet air temperature to 180°C, adjust the feed rate to an outlet air temperature of 90°C, adjust the spray pressure to a particle size of 200-400 nm, spray dry and collect the feed liquid to obtain sodium iron pyrophosphate particles A;
[0034] S2: Weigh ferric nitrate, sodium acetate, ammonium dihydrogen phosphate, and glucose (wherein the mass ratio of Na:Fe:P is 4.2:2.8:4, and the mass of glucose is 10% of the total mass), and grind them in a deionized water medium to a particle size of 300-600 nm;
[0035] Perform spray drying: set the inlet air temperature to 160° C., adjust the feed rate so that the outlet air temperature is 100° C., spray dry and collect the material to obtain sodium iron pyrophosphate particles B;
[0036] S3: Add particles A and B into a high-speed mixer at a mass ratio of 1:1.8 and mix evenly to obtain a precursor material, then sinter the precursor material under inert atmosphere conditions, at a heating rate of 5°C / min, keep at 150°C for 60 min, 350°C for 90 min, and 800°C for 720 min, and then air flow crush to obtain a carbon-coated sodium iron phosphate pyrophosphate positive electrode material.
[0037] Example 2
[0038] The difference from Example 1 is that the carbon nanotubes in step S1 are all replaced by carbon black, and the remaining steps are the same as Example 1.
[0039] Embodiment 2:
[0040] The difference from Example 1 is that the organic carbon source glucose in step S2 is replaced by glucosamine (the mass of glucosamine is 10% of the total mass), and the remaining steps are the same as Example 1.
[0041] Embodiment 3:
[0042] The difference from Example 1 is that the organic carbon source glucose in step S2 is replaced by a polyethylene glycol-glucose composite carbon source (wherein the mass of polyethylene glycol is 4% of the total mass, and the mass of glucose is 6% of the total mass), and the remaining steps are the same as Example 1.
[0043] Embodiment 4:
[0044] The difference from Example 1 is that the raw materials of the iron source, sodium source and phosphorus source in steps S1 and S2 are replaced by ferric pyrophosphate, sodium carbonate and phosphoric acid instead of ferric nitrate, sodium acetate and diammonium phosphate, and the remaining steps are the same as in Example 1.
[0045] Embodiment 5:
[0046] The difference from Example 1 is that the mass ratio of Na:Fe:P in steps S1 and S2 is changed to 4:3:4, and the remaining steps are the same as Example 1.
[0047] Embodiment 6:
[0048] The difference from Example 1 is that the mass ratio of particles A and B is changed to 1:2, and the remaining steps are the same as Example 1.
[0049] Embodiment 7:
[0050] The difference from Example 1 is that the mass ratio of particles A to particles B is changed to 1:1.5, and the remaining steps are the same as those in Example 1.
[0051] Embodiment 8:
[0052] The difference from Example 1 is that the sintering process is a two-stage temperature increase: at a heating rate of 5°C / min, 350°C is kept for 90 minutes and 800°C is kept for 720 minutes. The remaining steps are the same as in Example 1.
[0053] Comparative Example 1:
[0054] The difference from Example 1 is that the particles A containing carbon nanotubes are not added, and the particles B are directly sintered to obtain the positive electrode material;
[0055] S1: Weigh ferric nitrate, sodium acetate, ammonium dihydrogen phosphate, and glucose (wherein the mass ratio of Na:Fe:P is 4.2:2.8:4, and the mass of glucose is 10% of the total mass), and grind them in a deionized water medium to a particle size of 300-600 nm;
[0056] Perform spray drying: set the inlet air temperature to 160°C, adjust the feed rate so that the outlet air temperature is 100°C, spray dry and collect the material to obtain sodium iron pyrophosphate particles;
[0057] S2: The obtained sodium iron phosphate pyrophosphate particles are sintered under inert atmosphere conditions, with a heating rate of 5°C / min, and kept at 150°C for 60 min, 350°C for 90 min, and 800°C for 720 min, and then air flow crushed to obtain a positive electrode material.
[0058] Comparative Example 2:
[0059] The difference from Comparative Example 1 is that the organic carbon source glucose in step S1 is replaced by a polyethylene glycol-glucose composite carbon source (wherein the mass of polyethylene glycol is 6% of the total mass, and the mass of glucose is 9% of the total mass), and the remaining steps are the same as Comparative Example 1.
[0060] Comparative Example 3:
[0061] Preparation of carbon nanotube composite carbon source: weigh 5 parts of carbon nanotubes (tube diameter 10-50 nm), 1 part of polyvinyl pyrrolidone, and 94 parts of deionized water and disperse them evenly in a high-speed disperser to obtain a carbon nanotube composite carbon source;
[0062] The difference from Comparative Example 1 is that the organic carbon source glucose in step S1 is replaced by a polyethylene glycol-glucose-carbon nanotube composite carbon source (wherein the mass of polyethylene glycol is 4% of the total mass, the mass of glucose is 6% of the total mass, and the remaining 5% is the above-mentioned carbon nanotube composite carbon source), and the remaining steps are the same as Comparative Example 1.
[0063] Electrochemical performance test:
[0064] In order to test the electrochemical properties of the material, a half-cell was prepared. The lithium-ion battery was prepared as follows: the prepared positive electrode material, conductive agent and PVDF binder were mixed with an appropriate solvent at a mass ratio of 8:1:1 to form a slurry, and then the slurry was evenly coated on aluminum foil, and then vacuum dried at about 100°C and pressed into a positive electrode sheet. Among them, the negative electrode sheet is a sodium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is a NaPF6 ethylene carbonate / dimethyl carbonate solution, which are assembled into button batteries.
[0065] The electrochemical performance test is as follows: at room temperature, charge at a constant current of 0.1C with a cut-off voltage of 4.2V; then charge at a constant voltage of 4.2V with a cut-off current of 0.01C. After standing still, discharge at a constant current of 0.1C to 2.0, record the discharge capacity, and then charge and discharge at 1C, the process is the same as 0.1C.
[0066] The positive electrode materials in each embodiment and comparative example were prepared into positive electrode sheets, and the compaction density and electrochemical performance of the positive electrode sheets were tested. The test results are shown in Table 1:
[0067] Table 1 Test data table
[0068]
[0069]
[0070] From Table 1 we can see that:
[0071] (1) The sodium iron phosphate pyrophosphate positive electrode material prepared by the present invention has good electrochemical properties, and a slight excess of sodium and a slight deficiency of iron have better material properties. Therefore, slightly reducing the iron content in the sodium iron pyrophosphate composite material can effectively avoid the formation of impurities in the composite phase;
[0072] (2) It can be seen from Example 9 that three-stage sintering can make the material performance better. This is because the volatilization of water and the reaction of carbon source in the material are separated, which can avoid the volatilization of water too quickly and cause a large amount of carbon to be taken away.
[0073] (3) From the comparison of the comparative examples, it can be seen that the introduction of carbon nanotubes and inorganic carbon sources can improve the electrochemical properties of the material. This is because the organic carbon source can refine the particles and improve the performance of the material. However, excessive refinement will lead to a decrease in the compaction density of the material, thereby reducing the energy density of the material. The inorganic carbon source will form a loose chain-like coating on the surface of the material as it decomposes at high temperature, resulting in a larger specific surface area and better compressibility, which has a good effect on improving the compaction and energy density of the material.
[0074] (4) By comparing Example 1 and Example 2, it can be seen that by introducing carbon nanotubes into the particle precursor A, the material is further improved due to the separate coating of the composite carbon source of carbon nanotubes and inorganic carbon source and the organic carbon source. The main reason is that carbon nanotubes, due to their relatively large length-to-diameter ratio, can easily form a conductive grid with the surrounding materials, so that the overall structure of the material forms a conductive network of lines and surfaces, thereby improving the ionic conductivity and electronic conductivity of the material, and at the same time increasing the compaction density of the material, thereby increasing the energy density of the material.
[0075] (5) It can be seen from Example 3 that in-situ nitrogen doping can be achieved during the calcination process. This method is based on atomic-level doping, which improves the uniformity of doped nitrogen. It can provide more active sites during the sodium ion deintercalation process, thereby improving the electrochemical performance of sodium ion batteries.
[0076] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-limiting from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
Claims
1. A carbon-coated sodium iron phosphate pyrophosphate positive electrode material, characterized in that: It comprises a sodium iron phosphate pyrophosphate matrix and a coating layer on the surface. The coating layer is a carbon coating layer. The coating layer content in the positive electrode material is 2-10%. Carbon nanotubes are also distributed in the carbon coating layer to form a conductive network.
2. The carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The carbon coating layer is also doped with nitrogen, and the content of nitrogen in the positive electrode material is 0.1-0.3%.
3. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The steps include: S1: weigh carbon nanotubes, inorganic carbon source, and dispersant, dissolve them in deionized water to obtain a mixed solution, weigh iron source, sodium source, phosphorus source, and chelating agent, add them to the mixed solution, stir evenly, and then spray dry to obtain sodium iron pyrophosphate particles A; S2: Weigh an iron source, a sodium source, a phosphorus source, and an organic carbon source, mix them, grind them in a deionized water medium, and then dry them to obtain sodium iron pyrophosphate particles B; S3: Particles A and B are mixed to obtain a precursor material, which is then sintered and air flow-milled to obtain a carbon-coated sodium iron phosphate pyrophosphate positive electrode material.
4. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The content of carbon nanotubes in the mixed solution of step S1 is 5-10%, the content of inorganic carbon source is 0-5%, and the content of dispersant is 0.5-2%. The mass ratio of the iron source, sodium source and phosphorus source is 2-3:3-4.5:
4. The carbon nanotubes and inorganic carbon source account for 2-6% of the total mass of particle A. The particle size of particle A is 200-400nm.
5. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: In step S1, the inorganic carbon source is one or two of carbon black and acetylene black mixed in any proportion, the dispersant is one or more of polyvinyl pyrrolidone, ethanol, sodium polyacrylate, hydroxyethyl cellulose, and polypropylene ether, and the chelating agent is one or more of oxalic acid, citric acid, phosphoric acid, sodium pyrophosphate, sodium metaphosphate, tartaric acid, and triethyl ethylenediaminetetraacetate.
6. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: In the step S1, the solid content of the liquid spray-dried is controlled between 10 and 30%, the air inlet temperature is 150 to 300° C., and the air outlet temperature is 85 to 120° C.; in the step S2, the mass ratio of the iron source, the sodium source, and the phosphorus source is 2 to 3:3 to 4.5:4, the organic carbon source accounts for 4 to 9% of the total mass of the particles B, and the particle size of the particles B is 300 to 600 nm.
7. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The organic carbon source in step S2 is an organic compound mainly composed of carbon and hydrogen elements, preferably an organic compound containing nitrogen atoms.
8. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 7, characterized in that: The organic carbon source is one or more of sucrose, glucose, starch, citric acid, vitamin C, polyethylene glycol, polyvinyl alcohol, preferably one or more of glucosamine, amino starch, amino polyvinyl alcohol or amino-terminated polyethylene glycol; the drying method is spray drying or drying, wherein the inlet air temperature of the spray drying is 150-300°C and the outlet air temperature is 85-120°C; the drying temperature is controlled at 60-150°C; The iron source is one or more of ferric phosphate, ferric pyrophosphate, iron powder, iron oxide powder, ferrous oxalate, ferrous acetate, ferrous sulfate, ferric nitrate, and ferrous chloride; the sodium source is one or more of sodium carbonate, sodium phosphate, sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium acetate, sodium oxalate, sodium bicarbonate, sodium sulfate, and sodium bicarbonate; the phosphorus source is phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ferric phosphate, ferric pyrophosphate, manganese phosphate, sodium phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate, One or more of sodium.
9. The method for preparing the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: In step S3, the mass ratio of particles A to particles B is 1:1-2.5, and the sintering is divided into two or three stages of heating, wherein 100-200°C is kept for 0-60min, 200-400°C is kept for 60-250min, and 400-950°C is kept for 600-12000min. The sintering atmosphere is an inert atmosphere.
10. Use of the carbon-coated sodium iron phosphate pyrophosphate positive electrode material according to claim 1 in sodium ion batteries.
Citation Information
Patent Citations
Mixed crystal type polyanionic phosphate positive electrode material for sodium ion battery and preparation method of mixed crystal type polyanionic phosphate positive electrode material
CN113675390A
Modified high-performance sodium ferric pyrophosphate sodium ion battery positive electrode material as well as preparation and application thereof
CN114975973A
Composite carbon source coated composite sodium ferric phosphate positive electrode material and preparation method thereof
CN116885150A
Polyanionic sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN118213494A
Positive electrode active material, preparation method thereof and battery
CN118676340A
Cited By
Positive electrode active material and preparation method thereof, positive electrode plate, sodium battery and energy storage device
CN120453354A
Low-alkalinity sodium ferric pyrophosphate positive electrode material and preparation method thereof
CN120809789A
High-entropy doped ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN122126820A
Composite sodium ferric phosphate positive electrode material, preparation method thereof, positive electrode and sodium ion battery
CN122540838A